Heterothallic sexual reproduction in three canker-inducing tree pathogens within the Fusarium torreyae species complex. (4th July 2018) - Zhou, Xue; O'Donnell, Kerry; Kim, Hye-Seon; Proctor, Robert H.; Doehring, Gail; Cao, Zhi-Min
ABSTRACT: Fusarium zanthoxyli and F. continuum are sister taxa that are the etiological agents of canker disease of prickly ash ( Zanthoxylum bungeanum ) in northern China. These two pathogens, together with F. torreyae, the causal agent of canker disease of the critically endangered conifer Florida torreya ( Torreya taxifolia ) from northern Florida and southwestern Georgia, constitute a novel clade, the F. torreyae species complex. To assess their reproductive mode, a polymerase chain reaction (PCR) assay targeting the MAT1-1 and MAT1-2 idiomorphs was designed and validated, using MAT sequences mined from the whole-genome sequence of the three F. torreyae clade pathogens and several closely related fusaria. Results of the MAT idiomorph PCR assay indicated that isolates of the three pathogens were MAT1-1 or MAT1-2 . When MAT1-1 and MAT1-2 isolates of each species were crossed on carrot agar, all of the F. zanthoxyli (N = 30) and F. continuum (N = 3) isolates tested were female fertile, yielding mature perithecia with viable ascospores. By comparison, only one pairing of the five different isolates of F. torreyae produced perithecia; however, the majority of the asci in this cross aborted or produced fewer than eight ascospores. Of the three temperatures tested (i.e., 22, 25, and 27 C), the optimal temperature for perithecium production was 22–25 C in F. zanthoxyli and 25 C in F. continuum and F. torreyae . Ascospore progeny from three separate crosses of F. zanthoxyli and F. continuum and one cross of F. torreyae were genotyped to assess whether they were the products of genetic recombination and sexual reproduction. Genotyping of 34–40 progeny from the F. zanthoxyli and F. continuum crosses confirmed that they were the products of sexual reproduction. However, only 36% of the progeny in the F. torreyae cross were recombinant, which was roughly half of the nonparental progeny expected with three markers segregating.